A fossil species of the primitive mymarid genus Borneomymar (Hymenoptera: Mymaridae) in Eocene Baltic amber - Engel, Michael S.; McKellar, Ryan C.; Huber, John T. (Novitates Paleoentomologicae, 2013)
A new fossil species of fairyfly (Hymenoptera: Chalcidoidea: Mymaridae) is described and figured from a well-preserved female in middle Eocene (Lutetian) Baltic amber as Borneomymar pankowskiorum Engel, McKellar, & Huber, new species.  This species represents the fourth genus from Baltic amber whose extant species now occur only in southeastern Asia, Australia and Madagascar.